Implementation of Discovery Learning to Enhance Early Childhood Cognitive Development in Science Education - Ulul Audia Azmi; Gunawan Gunawan; Nurhasanah Nurhasanah; Filsa Era Sativa (Indonesian Publication Center, 2025)
The issue of low cognitive ability in understanding science concepts is frequently encountered in early childhood education institutions, where instruction often tends to be passive. This study aims to analyze the effectiveness of implementing the Discovery Learning method in science instruction to enhance the cognitive abilities of children aged 5–6 years at TK Dewi Seruni, Ampenan, Mataram City. This research employed a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of 20 children from Group B. Data were collected through observation using standard cognitive development instruments, treatment implementation, and documentation. Data analysis included normality tests, homogeneity tests, and hypothesis testing using the Paired Sample T-test. The prerequisite test results indicated that the data were normally distributed and homogeneous. Hypothesis testing revealed a Sig. (2-tailed) value of 0.000 < 0.05 with a t-count of -17.706, indicating a significant difference between pretest and posttest scores. Additionally, an N-gain score of 0.30 was obtained, falling into the medium category. It was concluded that the Discovery Learning method has a significant and effective influence on improving early childhood cognitive development in science instruction, as it facilitates children's active involvement in concept discovery.